Konsep Dasar Self Disclosure dan Pentingnya Bagi Mahasiswa Bimbingan dan Konseling - Ifdil Ifdil (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
Self-disclosure is one important aspect of interpersonal communication, which needs to have counseling students as prospective counselor. The ability of the students to perform self-disclosure has an important contribution in achieving academic success and the success of their social interactions. A person who has high self-disclosure tends to express the views, ideas, or ideas clearly without hurting the feelings of others. Based on the account of the phenomenon of self disclosure neglected by students Counseling. This article tries to describe about the urgency of self-disclosure on student guidance and counseling. Furthermore, this article will describe matters related to the sense of self-disclosure, the benefits of self-disclosure, the characteristics and dimensions of self-disclosure, the factors that influence self-disclosure and urgency for counseling students.